ESTETIKA KARAKTER ANIMASI PADA MEDIA KOMUNIKASI SOSIAL DENGAN KATEGORI AUDIENCE REMAJA - Putra, Gede Lingga Ananta Kusuma; Yasa, Gede Pasek Putra Adnyana (Institut Bisnis dan Teknologi Indonesia, 2020)
Animation currently shows a fairly high level of flexibility due to the influence of increasingly rapid technological advances. An animation should ideally have aesthetic value, by knowing the aesthetic location in the animation, it is hoped that the social communication process will be more effective. In this article, we use a qualitative method by examining several existing animations, and using literature related to the cases raised in order to obtain more accurate data. Ethical values ​​are needed in a communication medium, in order to attract the attention of the target audience, so that the information contained in the media can be conveyed. Implementation of the aesthetic of animated characters can apply the principle of appeal, so that these characters become more attractive.